ANALYSIS OF CUSTOMER COMPLAINT HANDLING (Case Study) (The Indonesian Journal of Business Administration, 2019)
The quality of service provided by each Bank becomes a differentiator and becomes a consideration for customers to be loyal to the Bank. With increasing competition in the service and manufacturing sectors, the strategic focus has shifted to determining retention strategies for customers.. The speed of handling complaints is measured by SLA (Services Level Agreement), where each bank is required to settle customer complaints for a maximum of 20 working days. For this reason, the company has a great responsibility to be able to handle customer complaints in accordance with the established SLA (Services Level Agreement). Risk of reputation and even financial risk can arise if customer complaints are not handled quickly and accurately.The research method uses PDCA (plan, do check, action) to know how the business process can be a contious improvement. This research will showed what the effect from the complaint handling is too late with the root causes method. To given a feedback from the problem this research uses decision making tools as a Analytic Hierarchy Process.Purpose – Purpose of research is to Determine factor-factor made a complaint handling problem and provide reference to which effective complaint handling.Methodology/approach – In this research, using qualitative methods which aim to take a direct data, interviews and questionnaires. Findings – Results of this research, Research Limitation – In this research has been established limitations in conducting research. Keywords: Customer Complaint Handling, Services Level Agreement, Decision Making, Analytic Hierarchy Process.